The Proses Perkembangan Anak dalam Perspektif Psikologi Pendidikan Islam: Teori Tadarruj Ibnu Khaldun dan Teori Kognitif Piaget - Sofiyan Baihaki; Sri Panca Aryaningsih; Pratiwii, Era Mutiara; Gazi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the concept of tadarruj (reflection) in Ibn Khaldun's educational thought and Jean Piaget's cognitive development theory, and analyze their relevance to the Psychology of Islamic Religious Education. The study employed a qualitative library research method, with data sources drawn from accredited journal articles discussing both figures. The results indicate that Ibn Khaldun's tadarruj emphasizes gradual learning, repetition, hands-on practice, and a compassionate approach with the goal of developing a perfect human being. Meanwhile, Piaget's theory proposes four stages of cognitive development: sensorimotor, preoperational, concrete operational, and formal operational, with mechanisms of assimilation, accommodation, and equilibration. Both theories emphasize the importance of gradualism and readiness to learn in the educational process. Implications for the Psychology of Islamic Religious Education include the periodization of faith development, hands-on practice-based learning methods, evaluation of practical portfolios, and a non-violent educational approach.